BET Inhibition Upregulates SIRT1 and Alleviates Inflammatory Responses. Issue 14 (13th August 2015) - Kokkola, Tarja; Suuronen, Tiina; Pesonen, Maija; Filippakopoulos, Panagis; Salminen, Antero; Jarho, Elina M.; Lahtela‐Kakkonen, Maija
Abstract Control of histone acetylation is a part of the epigenetic mechanism that regulates gene expression and chromatin architecture. The members of the bromodomain and extra terminal domain (BET) protein family are a group of epigenetic readers that recognize histone acetylation, whereas histone deacetyl‐ ases such as sirtuin 1 (SIRT1) function as epigenetic erasers. We observed that BET inhibition by the specific inhibitor JQ1 upregulated SIRT1 expression and activated SIRT1. Moreover, we observed that BET inhibition functionally reversed the pro‐inflammatory effect of SIRT1 inhibition in a cellular lung disease model. SIRT1 activation is desirable in many age‐related, metabolic and inflammatory diseases; our results suggest that BET protein inhibition would be beneficial in treatment of those conditions. Most importantly, our findings demonstrate a novel mechanism of SIRT1 activation by inhibition of the BET proteins.